Analisis Pengaruh Experiental Marketing Dan Service Quality Terhadap Customer Loyalty Dengan Customer Satisfaction Sebagai Variabel Intervening Di Outlet Ayam Geprek Cip-Cip - Citra Nova Amalia; Nur Rokhman (Journal of Economics, Business, Accounting and Management, 2024)
This study aims to determine the direct effects of experiential marketing and service quality on customer satisfaction, as well as the direct effects of experiential marketing, service quality, and customer satisfaction on customer loyalty. Additionally, this research seeks to identify the indirect effects of experiential marketing and service quality on customer loyalty through customer satisfaction. The research was conducted at Ayam Geprek Cip-Cip. This is a quantitative study, with the population comprising all consumers of Ayam Geprek Cip-Cip, and the sample was selected using purposive sampling method. The sample size in this study was 200 respondents. The analysis technique used is the sobel test and path analysis carried out using IBM SPSS Statistics 25. The results of the study indicate that experiential marketing and service quality have a significant positive effect on customer satisfaction. Furthermore, experiential marketing, service quality, and customer satisfaction also have a significant positive effect on customer loyalty. Customer satisfaction mediates the relationship between experiential marketing and service quality on customer loyalty.